German and Lithuanian Security Police (1941–1944) - Bubnys, Arūnas (Genocidas ir rezistencija, 1997)
The aim of this article is to examine the structure and functions of the German Security Police and the SD and Lithuanian Security Police during the Nazi occupation. The author has drawn on documents from various archives on the activities of operational groups and the German and Lithuanian security police.